1993
DOI: 10.1007/bf02261240
|View full text |Cite
|
Sign up to set email alerts
|

Thyroidal handling of radioiodine in sea level residents exposed to hypobaric hypoxia

Abstract: In the present investigation thyroidal accumulation of radioiodine and its release were assessed by direct testing of thyroid function using radioactive iodine, in vivo, in sea level residents intermittently exposed to hypobaric hypoxia. Thyroidal accumulation of radioiodine and its turnover were examined daily for 14 days. Twelve healthy human male volunteers were divided into three groups, with an equal number of individuals in each group. A decompression chamber was used to expose each group of subjects to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…So far, the data obtained from both the cold and temperate climates have not been very conclusive as most of the studies have been done at high altitudes, where along with the temperature, factors such as hypobaric condition, changes in oxygen partial pressure, and increased ultraviolet radiation might affect the secretion of hormones. A study conducted in a hypobaric chamber demonstrated that a simulated altitude of 3810 m affects the TH level [28]. The studies are also influenced by the sleep pattern, dietary changes, and plasma volume shifts [29].…”
Section: Discussionmentioning
confidence: 99%
“…So far, the data obtained from both the cold and temperate climates have not been very conclusive as most of the studies have been done at high altitudes, where along with the temperature, factors such as hypobaric condition, changes in oxygen partial pressure, and increased ultraviolet radiation might affect the secretion of hormones. A study conducted in a hypobaric chamber demonstrated that a simulated altitude of 3810 m affects the TH level [28]. The studies are also influenced by the sleep pattern, dietary changes, and plasma volume shifts [29].…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that it has excitatory effects on almost all tissues and has a certain correlation with energy metabolism (proteins, sugars, and fats), thermoregulation, tissue differentiation, and growth and development of bodies ( Maria et al, 2019 ). Hypoxia at high altitudes leads to changes in thyroid function and structure ( Naeije, 2010 ); however, the results of previous studies on the changes in TH caused by hypoxia are inconsistent ( Rawal et al, 1993 ; Savourey et al, 2004 ; Barnholt et al, 2006 ). Thyroid function has been shown to be enhanced, weakened, or even unchanged, which is related to many factors such as the exposure mode of hypoxia, altitude, duration, and availability of altitude adaptive training.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in protein-bound iodine, fi rst reported in 1966 [ 47 ], has been confi rmed by observations of increased uptake and release of iodine from the thyroid gland [ 48 ]. Most authors agree that high altitude induces an elevation in plasma concentration of both free and total T4 fractions of thyroxin [ 30 , 47 , 49 -57 ].…”
Section: Thyroid Hormonesmentioning
confidence: 95%